A study on on-the-job training and employees productivity among medical assistants at Hospital Sultan Abdul Halim, Sungai Petani, Kedah Darul Aman / Noor Hidayah Ismail and Rossarina Muhammed - Ismail, Noor Hidayah; Muhammed, Rossarina (2010)
The purpose of this research is to investigate on-the-job training (OJT) among Medical Assistants in Hospital Sultan Abdul Halim (HSAH) in Sungai Petani, Kedah. On-the-job training (OJT) can be divided into two types that include structured and unstructured on-the-job training. Structured on-the-job training include is a planned and organized of training that is designed to increase the skills and abilities of the employees that include Job Instruction Training (JIT), coaching, mentoring and supervision from supervisor. Unstructured on-the-job training is an approach in which learners are 'thrown into' the work rather than supervision from another person. Questionnaire was prepared and a research had been conducted in the Hospital Sultan Abdul Halim (HSAH), Sungai Petani, Kedah. The result shows that most of the respondents agreed that structured on-the-job training can increasing their productivity compared to the unstructured on-the-job training. From this research, we found that the organization frequently used structured on-the-job training because it can improve productivity through skill and knowledge. As a conclusion, structured on-the-job training can give positive effects to the workers and organization through increasing their skills and ability to perform well in their job. This study also provides the recommendation that can be used by the organization and employees such as supervisor, coach, mentor and medical assistants.